Fostering global citizenship and SDG integration through COIL in Ibero- America - Falasca, Marina; de Prada, Elena; Cuevas Alvarez, María Cruz (Journal of International Students, 2026)
This article examines the outcomes of COIL en Clave ODS para la Educación Superior en Iberoamérica, a five-week online training program developed by STAR Argentina to equip higher education professionals across Latin America, the Caribbean, and Spain with the tools to integrate global citizenship and the Sustainable Development Goals (SDGs) into Collaborative Online International Learning (COIL) initiatives. The program employed a flipped classroom model combined with live, interactive sessions to foster intercultural collaboration and sustainability-oriented pedagogy through active and participatory learning strategies. The analysis of post-program survey responses and reflections indicates successful integration of content and a significant increase in participants’ confidence in designing intercultural, SDG-aligned COIL projects, thereby highlighting COIL as a potentially scalable strategy that supports educators in designing learning environments in which international students are positioned as active contributors to sustainability-oriented learning.